2014
DOI: 10.1002/htj.21123
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of Double Diffusive Mixed Convection Laminar Flow in Two Sided Lid Driven Porous Cavity

Abstract: This paper presents the numerical study of mixed convection in a two-sided lid driven porous cavity due to temperature and concentration gradients. The top and bottom walls are stationary and insulated. The left and right walls are moving at an equal velocity (V o ) in the same direction. The temperature and concentration are kept high at the right wall and low at the left wall. The governing equations are discretized using finite volume method. The pressure-velocity coupling is performed by the SIM-PLE algori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…In recent years, the double‐diffusive convection has become increasingly important due to its many applications in several real situations, involving waste disposal, contaminated groundwater, and so on see, for example, Lombardo et al, 1 Franchi and Straughan, 2 and Nie et al 3 It is a subject of growing interest that has attracted many researchers. For example, Jena et al, 4 Liu and Umavathi, 5 Umavathi and Mohite, 6 Agarwal et al, 7 Zhuang et al, 8 Liu et al, 9 Siddiqa et al, 10 Shankar et al, 11 Raghunatha and Shivakumara, 12 Altawallbeh, 13 Mahajan and Tripathi, 14 and counts into the books by Nield et al, 15 Straughan, 16 and Vafai 17 . Moreover, the convection with the chemical reaction and magnetic effects has been much attention by many authors, see, for example, Turkyilmazoglu et al, 18 Turkyilmazoglu, 19,20 Malashetty and Biradar, 21 Ghasemi et al, 22 Teamah et al, 23 Al‐Sulaimi, 24 Yu et al, 25 Israel‐Cookey et al, 26 Gautam and Narayana, 27 Deepika et al, 28 Ebiwareme and Israel‐Cookey, 29 Mishra and Kumar, 30 Mahajan and Tripathi, 31 and Shivakumara et al 32 Recently, Noon and Haddad 33 investigated the impacts of varying gravity and rotation that combined with the reaction effect on the double‐diffusive convection of the Darcy model in a porous material using the linear and nonlinear stability analysis when the layer heated from the bottom and salted from the above or below.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the double‐diffusive convection has become increasingly important due to its many applications in several real situations, involving waste disposal, contaminated groundwater, and so on see, for example, Lombardo et al, 1 Franchi and Straughan, 2 and Nie et al 3 It is a subject of growing interest that has attracted many researchers. For example, Jena et al, 4 Liu and Umavathi, 5 Umavathi and Mohite, 6 Agarwal et al, 7 Zhuang et al, 8 Liu et al, 9 Siddiqa et al, 10 Shankar et al, 11 Raghunatha and Shivakumara, 12 Altawallbeh, 13 Mahajan and Tripathi, 14 and counts into the books by Nield et al, 15 Straughan, 16 and Vafai 17 . Moreover, the convection with the chemical reaction and magnetic effects has been much attention by many authors, see, for example, Turkyilmazoglu et al, 18 Turkyilmazoglu, 19,20 Malashetty and Biradar, 21 Ghasemi et al, 22 Teamah et al, 23 Al‐Sulaimi, 24 Yu et al, 25 Israel‐Cookey et al, 26 Gautam and Narayana, 27 Deepika et al, 28 Ebiwareme and Israel‐Cookey, 29 Mishra and Kumar, 30 Mahajan and Tripathi, 31 and Shivakumara et al 32 Recently, Noon and Haddad 33 investigated the impacts of varying gravity and rotation that combined with the reaction effect on the double‐diffusive convection of the Darcy model in a porous material using the linear and nonlinear stability analysis when the layer heated from the bottom and salted from the above or below.…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive review of the literature concerning double‐diffusive convection in a fluid‐saturated porous medium may be found in the book by Mojtabi and Charrier‐Mojtabi 39 . The study of thermosolutal convection of a fluid‐saturated porous medium has attracted the attention of many researchers, see for example Rionero, 40‐42 Gaikwad and Dhanraj, 26 Gaikwad and Kouser, 34 Liu and Umavathi, 43 Umavathi and Mohite, 44 Jena et al, 45 Agarwal et al, 46 Attia et al, 30 and the book by Straughan 47 . However, most materials that possess a pronounced anisotropy in permeability such as soils or rocks may enhance the dispersion and diffusion significantly inside porous materials, compare Karmakar and Raja Sekhar 48 .…”
Section: Introductionmentioning
confidence: 99%
“…It is observed that, at a fixed Re and Gr , the angle of inclination increases the flow changes from traversing periodic pattern to half periodic pattern. Agarwal et al investigated the influence of Richardson number ( Ri ), Pr , and Darcy number on mixed convection in the double‐sided lid‐driven enclosure. It is observed that on varying the magnitude of Pr the heat transfer is strongly influenced whereas the flow behavior almost remains invariant.…”
Section: Introductionmentioning
confidence: 99%